Associations of Vitamin D and Vitamin K and Their Metabolites Across Four Regions of the Human Brain: The Memory and Aging Project (MAP) (FS05-02-19). (13th June 2019) - Fu, Xueyan; Patterson, Will; Dolnikowski, Gregory; Dawson-Hughes, Bess; Morris, Martha; Holland, Thomas; Booth, Sarah
Abstract: Objectives: Very little is known about the forms of vitamin D and vitamin K in the human brain. The objective of this study is to evaluate concentrations of vitamin D and vitamin K forms in human brain and their correlations across four human brain regions. Methods: Vitamin D [D3, 25(OH)D and 1, 25(OH)2D] and vitamin K [phylloquinone and menaquinone-4 (MK4)] concentrations were measured by LC/MS/MS and HPLC, respectively, in four brain regions from post-mortem samples obtained from participants in the Rush Memory and Aging Project ( n = 130, mean age 82 yrs, 81% female). The brain regions analyzed were the mid-frontal cortex (MF) and mid-temporal cortex (MT) [two regions important for memory in Alzheimer's Disease (AD)], the cerebellum (CR, a region not affected by AD), and the anterior watershed white matter (AWS, a region associated with vascular disease). The correlations among the vitamin forms across brain regions were calculated using Spearman rank order correlation coefficients. Significance was set at P < 0.001. Results: The average concentrations of vitamin D3, 25(OH)D and MK4 were 604 pg/g, 535 pg/g, and 3.4 pmol/g, respectively. 25(OH)D and MK4 were detected in >95% of the brain samples. Nearly 92% of 1, 25(OH)2D and 80% of phylloquinone samples had concentrations below the limit of assay detection (LOD) 1, 25(OH)2D = 20 ng/g, phylloquinone = 0.1 pmol/g). Vitamin D3 and 25(OH)D concentrations were positively correlated across all four regions (all Spearman r ≥ 0.78, P < 0.0001). The 1, 25(OH)2D was significantly correlated between the MF and CR regions only (Spearman r = 0.30, P < 0.001, all other P ≥ 0.002). MK4 and PK were positively correlated across the four regions studied (MK4 all Spearman r ≥ 0.78, phylloquinone r ≥ 0.49, all P < 0.001). Conclusions: To the best of our knowledge, this study is the first evaluation of the concentrations of vitamin D and vitamin K forms in multiple regions of the human brain. Overall, the vitamin D and vitamin K forms were each positively correlated across the four brain regions studied. Future studies are needed to clarify the roles of these nutrients in AD and dementia. Funding Sources: National Institute of Aging.